Impaired Local Translation of β-actin mRNA in Ighmbp2-Deficient Motoneurons: Implications for Spinal Muscular Atrophy with respiratory Distress (SMARD1). (21st August 2018) - Surrey, Verena; Zöller, Caren; Lork, Alicia Andrea; Moradi, Mehri; Balk, Stefanie; Dombert, Benjamin; Saal-Bauernschubert, Lena; Briese, Michael; Appenzeller, Silke; Fischer, Utz; Jablonka, Sibylle
Highlights: Ighmbp2 deficiency marginally affects differentiation and function of primary motoneurons. Ighmbp2 deficiency leads to delayed β-actin protein biosynthesis at motor nerve endings. β-Actin down-regulation corresponds to reduced IMP1/ZBP1, but does not require Ighmbp2 binding to β-actin mRNA. No global changes on RNA and protein level are observed in Ighmbp2-deficient motoneurons. Abstract: Spinal muscular atrophy with respiratory distress type 1 (SMARD1) is a fatal motoneuron disorder in children with unknown etiology. The disease is caused by mutations in the IGHMBP2 gene, encoding a Super Family 1 (SF1)-type RNA/DNA helicase. IGHMBP2 is a cytosolic protein that binds to ribosomes and polysomes, suggesting a role in mRNA metabolism. Here we performed morphological and functional analyses of isolated immunoglobulin μ-binding protein 2 (Ighmbp2)-deficient motoneurons to address the question whether the SMARD1 phenotype results from de-regulation of protein biosynthesis. Ighmbp2-deficient motoneurons exhibited only moderate morphological aberrations such as a slight increase of axonal branches. Consistent with the rather mild phenotypic aberrations, RNA sequencing of Ighmbp2-deficient motoneurons revealed only minor transcriptome alterations compared to controls. Likewise, we did not detect any global changes in protein synthesis using pulsed SILAC (Stable Isotope Labeling by Amino acids in Cell culture), FUNCAT (FlUorescent Non-Canonical Amino acid Tagging) and SUnSET (SUrface SEnsing of Translation) approaches. However, we observed reduced β-actin protein levels at the growth cone of Ighmbp2-deficient motoneurons which was accompanied by reduced level of IMP1/ZBP1, a known interactor of β-actin mRNA. Fluorescence Recovery after Photobleaching (FRAP) studies revealed translational down-regulation of an eGFP- myr -β-actin 3′UTR mRNA in growth cones. Local translational regulation of β-actin mRNA was dependent on the 3′ UTR but independent of direct Ighmbp2-binding to β-actin mRNA. Taken together, our data indicate that Ighmbp2 deficiency results in local but modest disruption of protein biosynthesis which might partially contribute to the motoneuron defects seen in SMARD1.